O Teatro de Plínio Marcos: Linguagem e Mascaramento Social. - Versa, Cezar Roberto (2007)
The 60´s and 70´s of the century XX represents a period of vast artistic and cultural production in Brazil, however the censorship was the largest dilemma found by the artists, writers and playwrights, who had their productions forbidden. In the theater, great writers produce in that time, like Nelson Rodrigues (1912-1980), Jorge Andrade (1922-1994), and Plínio Marcos (1933 -1999); each one in his style, all censured by their productions. This research presents a study about the play Dois perdidos numa noite suja (1966), by Plínio Marcos, which shows the conflicts of the minority and marginalized social groups in the society. With a language full of slangs and obscene words, the plays by Plínio Marcos scared, so much the ones that saw them as the authorities that understood such procedure as an insult to the regime, because such situation revealed a disorder process inside of the order instituted by the military government. His plays reveal a segment of Brazil where the individuals need to face a world without perspective and hope. His plays created to be transitory images of a moment of turbulence became a perennial picture of a social and economical structure. However, it should be emphasized that Plínio Marcos' intention, as the own author says, was not merely to protest, because he understood that his productions showed the people as they were and what they said. Starting from this reflection, it is postulated in this dissertation the countercultural aspect of the language explored in the plays by the playwright. It is intended, this way, to contemplate as the language became inside of Plínio Marcos' dramatic text a tool of execration of dilemmas and social-historical-cultural conflicts of Brazil from the 60´s until the end of the years 70´s. The process of the revealing of a crude language it sustained in the continuous use of slangs and bad words, wanting to reach the other or the own society. To understand that process, it is used concepts like: dialogy, polyphony and carnavalization from the theory by Bakhtin, therefore in the bowl of Plínio Marcos characters' language there is a series of voices, that they carry ideologies asserted by the social reality in that they live, besides emphasizing the use of the language while a combat weapon to the busy position in the society, where the slang and the bad words aim to hurt or to lower the other in a dialogue. Nowadays, the slangs are classified inside of the perspective of the special languages. Methodologically, the work is supported in a bibliographical and documental research, in that newspapers and magazines of the time will serve as mark for the revision of the playwright's critical fortune, and that authors of the extent of the language, of the sociology, of the anthropology, of the literature and of the theater they will base the theoretical basis, like Magaldi (1998), Bornheim (1992), Schwarz (1992), Artaud (2006), DaMatta (1997), Preti (1981), Adorno and Horkheimer (1985), among others. It done the bibliographical and documental revision, the leading of the theoretical concepts will happen in the analysis of the play, study object, Dois perdidos numa noite suja (1966), by Plínio Marcos. It is very important to emphasize that the analysis is based and it is evidenced starting from the dramatic text and not in their staging ways and dramacity of the accomplished editing. Starting from the text to elucidate like the text is vast and complete, although full of a colloquial tone language, in that the informality and the delinquency glow as central axes.